Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1723
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Acoustic-Lexical Deep Learning Approach for Deception Detection

Abstract: Automatic deception detection is an important problem with far-reaching implications for many disciplines. We present a series of experiments aimed at automatically detecting deception from speech. We use the Columbia X-Cultural Deception (CXD) Corpus, a large-scale corpus of within-subject deceptive and non-deceptive speech, for training and evaluating our models. We compare the use of spectral, acoustic-prosodic, and lexical feature sets, using different machine learning models. Finally, we design a single h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 15 publications
2
26
0
1
Order By: Relevance
“…In particular, deep learning approaches to fusion appear to be particularly promising. For example, Mendels et al (2017) presented a single hybrid deep model with both acoustic and lexical features trained jointly and found that this approach to fusion achieved stateof-the-art results for deception detection. However, deep learning is not currently a good approach for depression detection, since labeled corpora are not very large and interpretable models are important.…”
Section: Existing Fusion Approachesmentioning
confidence: 99%
“…In particular, deep learning approaches to fusion appear to be particularly promising. For example, Mendels et al (2017) presented a single hybrid deep model with both acoustic and lexical features trained jointly and found that this approach to fusion achieved stateof-the-art results for deception detection. However, deep learning is not currently a good approach for depression detection, since labeled corpora are not very large and interpretable models are important.…”
Section: Existing Fusion Approachesmentioning
confidence: 99%
“…Research has shown that the veracity of verbal statements can be assessed automatically [60,107]. Among other speech cues, acoustic-prosodic features (e.g., formant frequencies, speech intensity) and lexical features (e.g., verb tense, use of negative emotion words) were found to be predictive of deceptive utterances [67]. Increased changes in speech parameters were observed when speakers are highly motivated to deceive [98].…”
Section: Deception Detectionmentioning
confidence: 99%
“…Given the results from baseline models and previous literature (Mendels et al, 2017;Levitan et al, 2016), we train Bidirectional Long Short-Term models (BiLSTM, Schuster and Paliwal, 1997;Zhang et al, 2015) with sequences of word embeddings, Multi-Layer Perceptrons (MLP) with acoustic feature sets, and the combinations thereof. The GloVe embeddings were used to initialize the weights but back propagation was also allowed to update embedding values during training.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…and concatenate embeddings learned from acoustic features passed through an MLP and those passed through a BiL-STM for the last softmax layer. The combined model structure follows Mendels et al (2017) except that we used 4 hidden layers for MLP, and concatenated additional individual features before the last softmax layer. Our model consists of four fully connected layers, each with 680 hidden units followed by ReLU (Krizhevsky et al, 2012) activations.…”
Section: Deep Learning Modelsmentioning
confidence: 99%